Pendampingan dan Bantuan Teknis Perencanaan Masterplan dan Bangunan TK Teratai ULM di Banjarbaru - Wastuty, Prima Widia; Sa’ud, Mohammad Ibnu; Hadinata, Irwan Yudha; Heldiansyah, J. C.; Aufa, Naimatul; Muchamad, Bani Noor; Mentayani, Ira; Sarbini, Gusti Novi (Universitas Nusantara PGRI Kediri, 2024)
Teratai Banjarbaru Kindergarten (TK) is one of the early childhood education institutions located in Banjarbaru. The situation of the Teratai Kindergarten building and environment technically does not meet the standards for facilities and infrastructure for organizing Kindergartens (TK) as regulated in the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia number 47 of 2023. The purpose of this activity is to organize the TK building and environment, as well as facilities and infrastructure in accordance with applicable guidelines and standards. The results of the activity are in the form of a Teratai Kindergarten Masterplan, building design and DED. These drawing documents are used by partners to submit funds for the construction of Teratai Kindergarten, and are a requirement in submitting a Building Approval for the construction of the building later.